Combat Drones & Legal Framework : A Military Revolution Yet to be Regulated - Arief Fahmi Lubis (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
The development of combat drones has brought a military revolution in the modern era, enabling military operations with global reach, high precision, and minimal risk to human personnel. However, this innovation raises serious legal challenges, as international humanitarian law (IHL) and traditional norms of warfare have yet to specifically regulate the use of autonomous weapons and long-range strikes. This study employs a qualitative approach based on document analysis, conflict case studies, and legal literature to explore the interaction between military operational logic and international legal principles. The findings indicate that legal boundaries in the use of combat drones often exist in a gray area, where considerations of military necessity and operational effectiveness may conflict with principles of civilian protection and proportionality. Furthermore, the legitimacy of drone use is influenced by public opinion, diplomatic pressure, and international accountability. This article emphasizes that the use of combat drones necessitates adjustments in international law and regulation, as well as a multidisciplinary approach integrating law, technology, and military sociology.